Personal finance building your future - Walker, Robert B.; Walker, Kristy P. (McGraw-Hill/Irwin series in finance, insurance and real estate, 2013)
Offers a timely discussion of living within one's means and incorporating personal values and priorities into a personal financial plan. This title intends to help readers set priorities that guide their finances, rather than the other way around